2014
DOI: 10.1590/s0100-40422014000100014
|View full text |Cite
|
Sign up to set email alerts
|

Dft theoretical study of energetic nitrogen-rich C4N6H8-n(NO2)n derivatives

Abstract: n (n = 1-6). The heats of formation (HOFs) were calculated by isodesmic reactions, and the detonation properties were evaluated using the Kamlet-Jacobs equations. The bond dissociation energies were also analyzed to investigate the thermal stability and sensitivity of the compounds. The results show that all of the derivatives have high positive HOFs, compound G has the highest theoretical density, and compound F1 has the highest detonation velocity and detonation pressure. Considering both the detonation prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Previous studies also demonstrated it as a feasible way in estimation accurate HOFs of novel energetic materials. This is because the electronic environment of atoms in the reactants and products is very similar in isodesmic reactions, the errors of electronic correction energies can be counteracted, and then the errors of the calculated HOFs can be greatly reduced [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies also demonstrated it as a feasible way in estimation accurate HOFs of novel energetic materials. This is because the electronic environment of atoms in the reactants and products is very similar in isodesmic reactions, the errors of electronic correction energies can be counteracted, and then the errors of the calculated HOFs can be greatly reduced [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon was consistent with the effect that the increasing number of nitro group will improve energetic properties effectively while it will decrease the stability of a compound evidently. 38…”
Section: Figure 6 Hofs Of the Designed Compoundsmentioning
confidence: 99%
“…It can be concluded that N1 and N14 are less reactive compared to that of N8 and N13 due to the space steric effect of the nitro group and intramolecular hydrogen bonds effects [30] of O7···H2 and O22···H18. Therefore, compounds E2 (ρ = 1.91 g cm -3 ; D = 9.2 km s -1 ; P = 39.2 GPa) and E3 (ρ = 1.96 g·cm -3 ; D = 9.8 km·s -1 ; P = 44.0 GPa) [31] might be possible to be synthesized rather than compounds E4-E7. ; D = 9.8 km s -1 ; P = 44.0 GPa) were also screened as the potential high energy density compounds based on the selectivity of nitration.…”
Section: Articlementioning
confidence: 99%